2013
DOI: 10.1007/s10447-013-9204-x
|View full text |Cite
|
Sign up to set email alerts
|

Practise What you Preach: Counsellors’ Experience of Practising Buddhist Counselling in Thailand

Abstract: This thesis is concerned with an exploration of counsellors' and clients' lived experiences of Buddhist Counselling, an indigenous Buddhist-based counselling approach in Thailand. Over the past decade, Buddhist Counselling has received a growing interest from Thai counselling trainees and practitioners, and it has also expanded to serve Thai people in various settings.Research on Buddhist Counselling is very limited and most of the existing studies in the field have focused on measuring the effectiveness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 179 publications
2
7
0
Order By: Relevance
“…The finding on the benefit of a collaborative partnership between counsellor and client for the success of mindfulness highlights the important role that counsellors hold in the successful integration of mindfulness into the treatment of depression and anxiety. A similar pattern of results was obtained in Schrinalli and Prior (2013), which found that counsellors maintaining a state of acceptance and awareness while guiding their clients through mindfulness techniques allowed them to be more aware of their clients’ experiences throughout the session, and this facilitated clients’ insight into their own experience. Further research could determine what clients perceive are the personal benefits of having a counsellor collaboratively involved in their mindfulness practice.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The finding on the benefit of a collaborative partnership between counsellor and client for the success of mindfulness highlights the important role that counsellors hold in the successful integration of mindfulness into the treatment of depression and anxiety. A similar pattern of results was obtained in Schrinalli and Prior (2013), which found that counsellors maintaining a state of acceptance and awareness while guiding their clients through mindfulness techniques allowed them to be more aware of their clients’ experiences throughout the session, and this facilitated clients’ insight into their own experience. Further research could determine what clients perceive are the personal benefits of having a counsellor collaboratively involved in their mindfulness practice.…”
Section: Discussionsupporting
confidence: 79%
“…Counsellors who maintain a personal practice of mindfulness are more likely to integrate the use of the technique into their clinical work. A qualitative research study conducted by Scrichannili and Prior (2013) examining counsellors’ experiences of practising Thai Buddhist counselling indicated that personal interest in mindfulness heavily influences the frequency and type of mindfulness techniques the counsellor uses in their clinical work. Five participants took part in a focus group, and in‐depth semi‐structured interviews were designed to explore their experiences.…”
Section: Practice Provides Understanding Of Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous adaptations could include Buddhist teachings as the rationale for couple therapy procedures and involve joint religious activities when appropriate. Buddhist influenced individual therapy already is influential in Thailand (Srichannnil & Prioir, 2014), and Buddhist influenced couple therapy should be evaluated in future research with Buddhist couples.…”
Section: Implications and Applicationsmentioning
confidence: 99%
“…In terms of helping others, for example, Buddhist monks are considered able to take a detached and objective view of issues and problems, and (like school counsellors) are often turned to for advice and support. It has been noted already that there is a tradition of providing informal counselling and support in Buddhist communities (Srichannil & Prior, 2013).…”
Section: Conceptual Aspectsmentioning
confidence: 99%